PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTU MEDIA BILANGAN JAM TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS III SDN 16 KOTO BARU - Ratnawati; Lika Apreasta; Ratul Jannah (STKIP Subang, 2024)
This research is based on problems in Mathematics learning in the discussion of addition materials, where the learning outcomes in mathematics subjects are low, students do not pay attention to the teacher when explaining the learning material, and lack of using creative and innovative learning media. Through this problem, the purpose of this study is to compare the learning outcomes of students taught using the Problem Based Learning (PBL) model assisted by the media of the number of hours with the learning outcomes of students taught using conventional learning in mathematics in grade III of SDN 16 Koto Baru. This study uses quantitative research with the type of Quasi Experiental Design research, using a Nonequivelent Control Group Design research design. This research was carried out at SDN 16 Koto Baru in grades IIIA and IIIB in the even semester of the 2023/2024 school year. The population in this study is 31 students in class IIIA and 31 students in class IIIB. The data collection instruments used are test questions, observation sheets and documentation. The development of instruments used is validity test, reliability test, problem difficulty test and discriminating power test. The data collection techniques used were the initial test (pretest) and the final test (posttest). The data analysis techniques of this study used normality tests, homogeneity tests and hypothesis tests. Based on the results obtained from the paired samples t test, which is 0.000<0.05, it means that it is rejected and Ha is accepted. Therefore, it can be concluded that there is an influence of the Problem Based Learning (PBL) model assisted by the media of the number of hours on the learning outcomes of mathematics in the third grade students of SDN 16 Koto Baru.